CLINICAL SIGNIFICANCE OF CYTOMEGALOVIRUS INFECTION IN PEDIATRIC LIVER TRANSPLANT RECIPIENTS - O. M. Tsiroulnikova; I. V. Zhilkin; D. G. Akhaladze (Вестник трансплантологии и искусственных органов)
Liver transplantation is a life-saving procedure for many forms of end-stage liver disease in pediatrics. Cytomegalovirus (CMV) is the most common and signifi cant posttransplant infection after pediatric liver transplant (PLT) with developing an episode of CMV infection or disease. It is well known that CMV increases risk of graft loss. The review presents aspects of etiology and epidemiology of CMV after PLT, approaches employed in diagnostics and prophylaxis of CMV, algorithms for valganciclovir dosing and methods to prevent complications associated with CMV. The latest data on current prevention strategies in pediatric liver transplantation centers in the world are also presented.